PENGENDALI POSISI MOTOR DC DENGAN PID MENGGUNAKAN METODE ROOT LOCUS - Agus Nuwolo; Adhi Kusmantoro (MEDIA ELEKTRIKA, 2014)
Position control using a motor is important at this time, especially in the industry. This control is used to move the conveyor so that it will stop at a designated place. Another application is to move the robot arm to a certain position. The development of control technology is so rapid now allow control is done digitally. The resulting simulation can be used to design a PID controller algorithm. Root locus design results in a PID controller generates 13.6% overshoot and settling time of 0.0386 seconds. With the interference of external PID controller is still able to cope with disturbances. To improve the quality of DC motor position controller is recommended to use logic controller Fuzi (fuzzy logic). Keywords: control position, Motor DC, Root Locus